Níveis de adubação N-K do abacaxizeiro 'BRS Imperial' no extremo Sul da Bahia - Oliveira, Arlene Maria Gomes [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Fertilization has great effect on the production and quality of pineapple fruits. This study aimed to evaluate the effect of N and K2O levels in vegetative development, production and post-harvest fruit quality of pineapple ‘BRS Imperial '. Four levels of N (0, 160, 320 and 550 kg ha-1) and four levels of K2O (0, 240, 480 and 600 kg ha-1), in a randomized block design with five replicates, in 42 full factorial. The K2O levels positively influenced the length and mass of the plant and the number of seedlings per plant, while nitrogen levels influenced the leaf emergence and seedling mass. The N fertilization decreased the artificially induced flowering, while K increased flowering. The leaf mass 'D' showed the best correlation with fruit weight, being estimated a minimum mass of 44g to improve fruit 900g. Foliar N and K estimated at maximum doses tested were 13 g kg-1 and 32 g kg-1, respectively. The K did not influence the production variables. It was possible to register fruits with crown mass of 1086 g at the maximum dose of 365 kg ha-1 of N and yield of 42 t ha-1. The fertilization with N and without K increased the translucency linearly. With the increase of K, even at the highest dose of N, there was a decrease of the translucency of the fruits with a minimum point of 2.38 (on a scale of 1 to 5) physically, at a maximum of 400 kg ha-1 K2O. The N doses resulted linear decreases in SS and TA, while the pH and the ratio increased by increasing levels of N. The K2O levels increased linearly TA and SS, while the ratio decreased linearly. The fertilizer N promoted negative effects while potassium acted positively on the quality of 'BRS Imperial’ fruits

A adubação exerce grande efeito na produção e qualidade dos frutos de abacaxizeiro. Este trabalho teve como objetivo avaliar o efeito de doses de N e K2O no desenvolvimento vegetativo, na produção e na qualidade pós-colheita dos frutos de abacaxizeiro ‘BRS Imperial’. Foram testadas quatro doses de N (0, 160, 320, 550 kg ha-1) e quatro doses de K2O (0, 240, 480 e 600 kg ha-1), em um delineamento de blocos ao acaso, com cinco repetições, em fatorial completo 42. As doses de K2O influenciaram positivamente a massa e comprimento da planta e no número de mudas por planta, enquanto as doses de N influenciaram na emissão de folhas e na massa de mudas. A adubação com N diminuiu o percentual de florescimento induzido artificialmente, enquanto o K aumentou o florescimento. A massa da folha ‘D’ apresentou a melhor correlação com a massa do fruto, sendo estimada a massa mínima de 44g para obtenção de frutos de 900g. Os teores foliares de N e K estimados, nas doses máximas testadas, foram 13 g kg-1 e 32 g kg-1, respectivamente. O K não influenciou nas variáveis de produção. Observaram-se frutos com coroa de massa de 1086 g na dose máxima de 365 kg ha-1 de N e produtividade de 42 t ha-1. O aumento da adubação com N e sem K, aumentou a translucidez de forma linear. Com o aumento de K, mesmo com a maior dose de N, ocorreu uma diminuição da translucidez dos frutos, com um ponto de mínimo de 2,38 (em uma escala de 1 a 5) na dose máxima física de 400 kg ha-1 de K2O. As doses de N promoveram decréscimos lineares nos SS e na AT, enquanto o pH e o ratio aumentaram com o incremento das doses de N. As doses de K2O aumentaram linearmente a AT e os SS, enquanto o ratio decresceu linearmente. A adubação com N promoveu efeitos negativos enquanto a potássica atuou de forma positiva na qualidade dos frutos de ‘BRS Imperial’
Keywords: Abacaxi - Adubação; Abacaxi - Nutrição; Fertilizantes nitrogenados; Fertilizantes potássicos; Produtividade agrícola; Pineapple